Experimental study of laminar natural convection heat transfer from a vertical cylinder to slush nitrogen under constant heat flux conditions. (October 2015) - Lee, Yoonseok; Ikeuchi, Masamitsu
Highlights: Free convection in slush nitrogen (SlN2 ) under constant heat flux conditions is investigated. Heat transfer is better for SlN2 than for subcooled liquid nitrogen (LN2 ). Solid N2 particles near the heater suppress the increase of heater temperature. Solid N2 particles below the heater facilitate convection flow. Solid N2 particles near the heater do not discourage local convection. Abstract: Natural convection heat transfer from a vertical cylinder immersed in slush and subcooled liquid nitrogen and subjected to constant heat fluxes was investigated in order to determine the relative merits of slush nitrogen (SlN2 ) for immersion cooling. A glass dewar was used as a test vessel in which a cylindrical heater was mounted vertically, and heat transfer measurements were carried out for SlN2 and subcooled liquid nitrogen (LN2 ) in the laminar flow range. The results revealed advantages of SlN2 over subcooled LN2 in natural convection cooling. The local temperatures of the heated surface surrounded by solid nitrogen particles are measured to increase at much slower rates than in subcooled LN2, which is due to the latent heat of fusion of solid nitrogen. Even after the solid nitrogen particles surrounding the heater are apparently depleted, the average heat transfer coefficients for SlN2 are still found to be greater than those for LN2 with the improvement in heat transfer being larger for lower Grashof number regime. Our analysis also indicates that solid nitrogen particles in close proximity to heated surface do not discourage local convection due to the porous nature of SlN2, making the heat transfer in SlN2 more effective than in the case of solid–liquid phase change of nitrogen involving melting and conduction processes.